Analisa Penerapan Metode Operational Competitiveness Rating Analysis (OCRA) dan Metode Multi Attribute Utility Theory (MAUT) Dalam Pemilihan Calon Karyawan Tetap Menerapkan Pembobotan Rank Order Centroid (ROC) - Abdul Karim; Shinta Esabella; Kusmanto Kusmanto; Mesran Mesran; Uswatun Hasanah (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
For companies, employees are an important aspect that must be supported by quality human resources. In the selection of permanent employees, usually the leadership in a company conducts an objective selection process in accordance with predetermined criteria. However, leaders often face several problems in this process, such as the selection is carried out in stages so that it takes a long time and the assessment of prospective employees is still done manually, making mistakes often occur. Therefore, a decision support system is needed as a solution to these problems by applying a comparison of the Operational Competitiveness Rating Analysis (OCRA) method and the Multi Attribute Utility Theory (MAUT) method and the weighting obtained by the Rank Order Centroid (ROC) method. The test results obtained the best alternative that is considered feasible as a permanent employee is in the same alternative, namely A5 on behalf of Risa Sabrani. The OCRA method produces the best preference value of 1.56 while the MAUT method produces the best preference value of 0.456 as the first rank